The effectiveness of the national anti-corruption policy of Ukraine - Kotukov, Oleksandr; Kotukova, Tetiana; Kozlov, Konstantyn; Makarenko, Oleksandr; Odyntsova, Olena (Amazonia Investiga, 2023)
An effective national anti-corruption policy is one of the means of improving the legal mechanisms of compliance with the guarantees of human rights and freedoms at the national level. The corruption rate in the public sector reflects the state of development of Ukraine as an economic and legal state and its place in the international arena. The aim of the study was to analyse the state anti-corruption policy of Ukraine and the effectiveness of its implementation mechanisms. Empirical and theoretical methods of scientific knowledge, as well as the method of comparative analysis, were used for a comprehensive study of the issue under research. The system of measures for the implementation of Ukraine’s anti-corruption policy has become an effective tool for preventing and countering corruption. Effective anti-corruption measures in Ukraine were: coordinated state anti-corruption strategy; the newly created structure of anti-corruption bodies; virtuous public service; implemented electronic systems for public procurement and property management; regular public reporting; independence of the prosecutor’s office and judiciary; monitoring and control of civil society. Further studies may focus on determining and justifying the impact of the anti-corruption policy on the comprehensive development of the state with the purpose of providing practical recommendations for the implementation of anti-corruption measures.